INDIKASI PERILAKU EXCESSIVE PRICING PRODUK BAHAN POKOK GULA BERDASARKAN UU NOMOR 5 TAHUN 1999 - Monica Angelia Hariono, Monica Angelia Hariono (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2024)
The scarcity of sugar supply in the market ahead of Hari Raya is an act of spontaneity by MSME traders to take advantage of the scarcity of sugar in the market by increasing the price of sugar. Although the price is still within the purchasing ability of the community as a whole, it does not rule out the possibility that the price of sugar is burdensome for a number of other small communities. This also implies that if this continues, without any concrete action from the Government, the price of Sugar will reach the Highest Unreasonable Price which allows a large number of people to no longer be able to spend that amount of money just to buy Sugar and this indicates that there has been an Excessive Pricing action by traders in the market or MSMEs (Micro, Small and Medium Enterprises) according to Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition.